2014
DOI: 10.4012/dmj.2013-303
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the remaining dentin thickness using optical coherence tomography for crown preparation

Abstract: This study aimed to investigate the maximum depth imaging and optical properties of the dentin near the pulp by using optical coherence tomography (OCT) and to explore the possibility of measuring the remaining dentin thickness (RDT). Human third molars were used. In experiment 1, the cuspal dentin blocks (0.50-mm to 1.75-mm thickness) were prepared. Each specimen was scanned using OCT. OCT images could be obtained for all specimens with 1.00-mm or less thicknesses. In experiment 2, dentin-pulp complex slices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…The remaining dentin thickness and pulp geometry, e.g., pulp horns, can be visualized in vitro during dental procedures using optical coherence tomography [56][57][58][59]. We found that the roof of the pulp chamber could be displayed using SD-OCT at a mean distance through dentin of 850 μm, whereas the minimum remaining dentin thickness which could be imaged was 45 μm (Figure 15), and is in accordance with Fonseca et al [57].…”
Section: Remaining Dentin During Caries Removalsupporting
confidence: 73%
“…The remaining dentin thickness and pulp geometry, e.g., pulp horns, can be visualized in vitro during dental procedures using optical coherence tomography [56][57][58][59]. We found that the roof of the pulp chamber could be displayed using SD-OCT at a mean distance through dentin of 850 μm, whereas the minimum remaining dentin thickness which could be imaged was 45 μm (Figure 15), and is in accordance with Fonseca et al [57].…”
Section: Remaining Dentin During Caries Removalsupporting
confidence: 73%
“…On the other hand, although previous literature has hinted at the potential application of OCT for RDT assessment (21,22), this approach needs to be validated against a standard technique for the measurement of RDT during removal of deep natural caries.…”
mentioning
confidence: 99%
“…SL was defined as the gold standard in this study, because section images were obtained non-destructively. Previous studies have reported the maximum dentin thickness penetrable by SS-OCT laser as <1.69 mm [5][6][7]9 . Other studies have reported the depth range of SS-OCT imaging in dental hard tissues as approximately 2.0 mm 10 .…”
Section: Discussionmentioning
confidence: 98%
“…As noted above, radiographic procedures possess some limitations. A few studies suggested that SS-OCT might detect the pulp dentin complex 5,6 . It has been reported that, using CT as a gold standard, spectral-domain OCT (SD-OCT), a type of OCT often employed in ophthalmology, successfully detected the pulp dentin complex 7 .…”
Section: Introductionmentioning
confidence: 99%